Simultaneous elimination of cationic uranium(vi) and anionic rhenium(vii) by graphene oxide–poly(ethyleneimine) macrostructures: a batch, XPS, EXAFS, and DFT combined study. Issue 9 (16th August 2018) - Huang, Zhi-Wei; Li, Zi-Jie; Wu, Qun-Yan; Zheng, Li-Rong; Zhou, Li-Min; Chai, Zhi-Fang; Wang, Xiao-Lin; Shi, Wei-Qun
Abstract : Free and protonated amino groups anchored on the macrostructures are responsible for U(vi ) and Re(vii ) adsorption, respectively. Abstract : In the field of radioactive wastewater treatment associated with environmental remediation, a big challenge is to achieve the simultaneous elimination of toxic metal cations and metallate anions. Herein, a three-dimensional (3D) graphene oxide-supported ethyleneimine polymer composite (GO–PEI) was synthesized by a self-assembly strategy and used for the simultaneous removal of cationic U(vi ) and anionic Re(vii ), which acts as a surrogate for Tc(vii ), from aqueous solution. The maximum adsorption capacity of GO–PEI composites at pH 5.0 for U(vi ) and at pH 3.5 for Re(vii ) was determined to be 629.5 and 262.6 mg g −1, respectively. Based on Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), extended X-ray absorption fine structure (EXAFS) analyses, and density functional theory (DFT) calculations, the adsorption of U(vi ) is predominantly attributed to the coordination with abundant amino and oxygen-containing groups anchored on the hydrogel. In contrast, the removal of Re(vii ) is correlated with the anion-exchange mechanism. In addition, GO–PEI has demonstrated a highly extractive adsorption capability toward U(vi ) in ultralow concentrations. Our work may pave the way for creating an exciting new category of material with versatile capabilities for the treatment of radioactive effluent from the nuclear fuel cycle.